A Report on Transfers from L. A. C. C. to the Various Campuses of the California State University and Colleges, 1972-1973. Research Study No. 74-7 - Gold, Ben K.; Los Angeles City Coll., CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This study summarizes (in three tables) the 1972-1973 performance of the first-time Los Angeles City College (L. A. C. C.) transfers at the various campuses of the California State University and Colleges. The following are some observations from the findings of the study: (1) 16 of the 19 campuses sent reports to L. A. C. C.; 14 reported at least one transfer from L. A. C. C. during 1972-1973; (2) three local campuses accounted for nearly 90 percent of the total reported number of 1,119 (Los Angeles 65 percent, Northridge 16 percent, Long Beach 8 percent, all others below 3 percent); (3) at 8 of the 11 campuses reporting fall 1972 entrants, grade point average (GPA) was higher at the state institution than at L. A. C. C. Over 40 percent of the total number of fall entrants earned a "B" average or above (50 percent for females) at the transfer institution; 15 percent earned below a "C" average (6 percent for females); (4) females' GPA for the fall 1972 entrants was 2.79, males 2.47, compared with respective L. A. C. C. GPA's of 2.59 and 2.45. Both groups improved their GPA at the state institution; and (5) transfers in the Schools of Letters and Science at the three local campuses averaged 2.6 or above; those in the Schools of Business averaged below 2.4; and the only group averaging below "C" (1.98) were seven Fine Arts transfers from Northridge. (Author/DB)
Educational level discussed: Higher Education.
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; College Students; Colleges; Community Colleges; Grade Point Average; Higher Education; Institutional Research; Postsecondary Education; Statistical Data; Tables (Data); Transfer Students; Universities; California; Numerical/Quantitative Data